The Relationship Between Fulfilment of Basic Needs with the Incidence of Stunting In Toddlers - Surani, Endang; Susilowati, Endang (Jurnal Ners, 2020)
Introduction: The prevalence of toddlers who very short and short at the age of 0-59 months in Indonesia is still high. One cause of stunting is lack of nutrition, mainly in the first 1000 days of life. The purpose of this study was to identify the relationship between the fulfilment of basic needs with the incidence of stunting in toddlers. Methods: A quantitative analytic research methods using cross-sectional approach was applied on this study. The sample was100 toddlers collected by purposive sampling technique. The questionnaires were used to measure the fulfilment of the basic needs of children and included questions about physical, emotion and stimulation. The data were analysed using Chi-Square. Results: There was a relationship between fulfilment of the basic needs in physical and emotion category with stunting (p value of 0.000), while there was no relationship between fulfilment of basic needs in the category of stimulation with stunting (p value of 0.090). Conclusion: The fulfilment of the basic needs of physical and emotion affects the condition of toddlers with stunting. Thus, all of children should get exclusive breastfeeding, appropriate complementary feeding, early childhood education programme, attend an Integrated Healthcare Centre routinely, have adequate access to immunisation services.